Jack Ryan [videorecording (DVD)] : shadow recruit - Branagh, Kenneth; Cozad, Adam; Koepp, David; Pine, Chris, 1980-; Costner, Kevin; Knightley, Keira, 1985-; Clancy, Tom, 1947-2013
A global action thriller set in the present day. This original story follows a young Jack as he uncovers a financial terrorist plot. When Ryan believes he's uncovered a Russian plot to collapse the United States economy, he goes from being an analyst to becoming a spy and must fight to save his own life and those of countless others, while also trying to protect the thing that's more important to him than anything, his relationship with his fiancé Cathy.